International handbook of local and regional government a comparative analysis of advanced democracies - Norton, Alan (Edward Elgar, 1994)
The Handbook offers a comparative analysis of local and regional government in a wide range of countries, discussing their histories, traditions, national and internal institutional structures, financing, competences and functions.